Tesis para ser publicada en revista - Valarezo Campoverde, Sergio Tulio (2015)
The objective of this project is the study and treatment system design of wastewater from the city of Macará. In 2001, with funding from the "Environmental Health Project (EHP)" or (Environmental Health Project) in Spanish, Sanitation Plan Macará hired within which comprises as a recommended treatment option and technical disposal of wastewater from the city of Macará, the artificial wetland system; thus accepting this recommendation the subsurface flow constructed wetlands are used. In research studies for the characterization of wastewater, topographic, demographic studies using the software DEMPROJ, preliminary studies, bases and design parameters, environmental impact assessment, operation, maintenance and control of the treatment plant, budget and schedule were works